The Nanosecond Frequency Electron Accelerator; EAPPC with BEAMS and MEGAGAUSS, 2016 Estoril [EAPPC 2016, 6th Euro-Asian Pulsed Power Conference ; BEAMS 2016, 21st International Conference on High-Power Particle Beams ; MG-XV, 15th International Conference on Megagauss Magnetic Field Generation and Rlated Tpics] - Nashilevskiy A. V. Aleksandr Vladimirovich; Ezhov V. V. Vitali Vladimirovich; Remnev G. E. Gennady Efimovich; Poloskov A. V. Artem Viktorovich; Kanaev G. G. Gennady Grigorevich; Egorov I. S. Ivan Sergeevich (2016, 2016)
В фонде НТБ ТПУ отсутствует